Kritik Ibnu Taimiyyah Terhadap Kedudukan Shaikh Dan Fungsi Khirqah Dalam Tarekat - Mulyadi Mulyadi (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
The term tasawwuf was known in the 2nd century and then in its development it started to enter a period of intuition, kashf, and dhauq. In this period, contrasts emerged from the two groups of tasawwuf, namely the sheikh and darvish groups where both were considered as groups that eliminated aspects of the tasawwuf experience that the previous Sufis embraced and understood. At this time there was a mujaddid al-Islam who was held with Shaikh al-Islam from the descendants of a woman named Taimiyyah, he was Ahmad Ibn Taimiyyah. His criticism of the deviant beliefs and behavior of the Sufis, especially the adherents of the tarekat, was very well known in his time and was part of his jihad in restoring the purity of Islam. Among the cases that became part of his criticism was the sheikh's position in the tarekat which he considered part of a form of cult towards pious people, besides that he also criticized the issue of khirqah which is part of the shi'ar of the Sufis as a symbol of obedience to the sheikh and a symbol of obedience to someone muris. in the tarekat. Both of these matters in the view of Ibn Taymiyah are something far from what Allah has outlined and taught by the Prophet Muhammad and previous pious scholars (Salaf al-saleh).